Facile fabrication of porous carbon microtube with surrounding carbon skeleton for long-life electrochemical capacitive energy storage. (15th July 2018) - Bao, Jinpeng; Liang, Chen; Lu, Haiyan; Lin, Haibo; Shi, Zhan; Feng, Shouhua; Bu, Qijing
Abstract: In this report, a hierarchical porous carbon microtubes (CMTs) coated by carbon skeleton was prepared simply and the better role of carbon skeleton in increasing the capacity of CMTs was also investigated. SEM, XRD and XPS were used to character the morphology, crystal structure and the functional group of CMTs and CMTs-coated carbon skeleton. Electrochemistry of materials was conducted by CV and constant-current techniques. The results show that the carbon skeleton improves the electric conductivity of materials and thus a better stability of capacity during charge and discharge was obtained (from 81.2 to 97.1% of original specific capacitance after 10000 GCD cycles at 1 A g −1 ), although the high specific surface area were altered weakly (1159 m 2 g −1 ). Besides, the incorporated nitrogen-containing functional group can increase the gravimetric capacitance of materials from 253 F g −1 to 278 F g −1, with the volumetric capacitance up to 152 F cm −3 . The adequate utilization of nature characteristic of biomass and the simple synthesis of stable carbon skeleton offers a good alternative route for advance CMTs. Highlights: Carbon microtube prepared via metaplexis was further optimised basing on previous work. Carbon microtube surrounding via carbon skeleton was synthesized via a facile method basing on the material above. The doped carbon shows excellent cycling stability and specific capacitance.